Nahdlatul Ulama as The Main Actor Managing and Resetting Civilization in The Digital Era - Ridho, Ali; Suja, Aidillah; Taufik, M.; Rahmat, Syahrul; Nisa, Faridhatun (Fakultas Ushuluddin Adab dan Dakwah IAIN Metro-Lampung, 2023)
The Nahdlatul Ulama (NU) organization was established on Rajab 16, 1344 (January 31, 1926), initiated by Hadratussyaikh KH. Muhammad Hasyim Asy’ari in Surabaya, Indonesia. NU, whose age has turned a century (one hundred years), considers that the understanding and mastery of literacy and technology in the digital era possessed by the Nahdliyin (the citizens affiliated to or members of NU) and the Indonesian general public occupy a fundamental position. It is not only within the scope of religion but also socio-political, cultural education, intolerance, stereotypes, radicalism, and terrorism threatening the unity and peace of the international world, the Indonesian nation, and the Nahdliyin in particular. This study employed the Q-DAS (Qualitative Data Analysis Software) approach incorporating a combined model of literature review and netnography on the “TVNU” YouTube channel, social media accounts of ulama (Kyai) of Nahdlatul Ulama, and moderate Islamic websites managed by cyber and network teams affiliated with Nahdlatul Ulama. The present research aimed to observe and analyze the role of NU as the main actor in reorganizing and creating harmony in humankind and realizing world peace by strengthening literacy in the digital era to commemorate the centenary of its establishment.